Daytime sleepiness in Parkinson's disease: a multifaceted symptom - Di Laudo, Felice; Baldelli, Luca; Mainieri, Greta; Loddo, Giuseppe; Montini, Angelica; Pazzaglia, Caterina; Sala, Monica; Mignani, Francesco; Provini, Federica (Frontiers in Sleep, 2023)
Excessive daytime sleepiness is a symptom experienced by more than one-third of patients with Parkinson's disease and is associated with disease duration and severity, dopaminergic therapy, and several non-motor symptoms. In recent years, growing evidence has been suggesting “primary” sleepiness as a symptom in Parkinson's disease due to common pathophysiological features: for this reason, it is crucial to recognize sleepiness in these patients and to investigate and exclude other conditions possibly leading to sleepiness (e.g., heavy dopaminergic therapy or breathing disorders during sleep). For both inpatients and outpatients, the key to a correct diagnosis is a structured clinical interview, together with questionnaires, for a better characterization of symptoms and the use of objective measures as the most precise method to assess excessive daytime sleepiness. Finally, there are some therapeutical approaches that may be attempted for these patients, and although there is still no consensus on a standardized therapy, clinical trials with new drugs are currently persevered on.